Delayed Diagnosis of Uterus Didelphys Unicolis with Cervical Atresia in a Forty-Three-Year Old Unmarried Woman with Primary Amenorrhea - Kale, Ahmet; Yalınkaya, Ahmet; Akdeniz, Nurten (Gynecology Obstetrics & Reproductive Medicine, 2006)
Müllerian duct fusion deficiency leads to uterus didelphys. We report the first case of a didelphysunicolis uterus with atretic cervix in a 43-y ear-old unmarried woman with a thirty years history of cyclic lower abdominal pain and primary amenhorrea. On abdomino-pelvic ultrasound examination, a diagnosis of pelvic mass was suspected. On exploratory laparotomy, a didelphys-unicolis uterus with atretic cervix was found. Total abdominal hysterectomy and right salpingectomy were performed. To our knowledge, such a late diagnosed uterine didelphys unicolis with cervical atresia case in a 44 years old unmarried woman with primary amenorrhea has not been previously reported